Study Of The Conversion Strategy Of PT. Bank Pembangunan Daerah Sulawesi South And West Sulawesi (PT. Bank Sulselbar) Into A Commercial Sharia Bank In Improving Business Performance (International Journal of Environmental Sciences, 2025)
This study aims to analyze the conversion model of PT. Bank Sulselbar into a Sharia Commercial Bank; examine the strategic opportunities and obstacles that influence the effectiveness of the conversion of PT. Bank Sulselbar into a Sharia Commercial Bank; and determine the implications of the conversion on improving the business performance of PT. Bank Sulselbar. This study uses a qualitative descriptive method with a field research approach to describe the conversion strategy of PT. Bank Sulselbar into a Sharia Commercial Bank and its impact on business performance. Primary data was obtained through interviews with management, employees, and customers, while secondary data came from written references. The research instrument was an interview checklist, with data collection techniques including interviews, observation, and documentation. Data analysis was carried out in stages, starting from reading transcripts, compiling specific messages, identifying patterns, and grouping data based on categories and typologies to draw conclusions. The results of the study indicate that: 1) The conversion of PT. Bank Sulselbar into a Sharia Commercial Bank was carried out directly in accordance with POJK No. 64/POJK.03/2016 and the P2SK Law, with a focus on institutional adjustments, capitalization, leadership, as well as the formation of a Sharia Supervisory Board and licensing documents. 2) This conversion opens up significant opportunities to expand the share of the sharia financial market, increase the trust of the Muslim community, and support national programs in South and West Sulawesi, although it still faces internal and external strategic obstacles. 3) The conversion also has a dual impact on business performance, strengthening the image and market of the Islamic economy, but simultaneously poses the risk of decreased liquidity, dependence on institutional depositors, and limited financing for the productive sector. The implications of this research have a significant impact on financial performance, risk management, and market penetration strategies, so that careful, measurable, and data-based planning is needed to ensure the success of the conversion strategy.